Answer:
see explanation
Step-by-step explanation:
Multiply through by the lowest common multiple of u, v and f, that is uvf
uvf × [tex]\frac{1}{v}[/tex] + uvf × [tex]\frac{1}{u}[/tex] = uvf × [tex]\frac{1}{f}[/tex], that is
uf + vf = uv ← factor out f on the left side → (1)
f(u + v) = uv ← divide both sides by (u + v)
f = [tex]\frac{uv}{u+v}[/tex]
(b)
Using line (1)
uf + vf = uv ( subtract uv from both sides )
uf + vf - uv = 0 ( subtract uf from both sides )
vf - uv = - uf ← factor out v on the left side
v(f - u) = - uf ← divide both sides by (f - u)
v = - [tex]\frac{uf}{f-u}[/tex]
Grade 6,7, and 8 at a middle school each have 180 students. The student council is throwing a school dance and they want to know what Theme to have for the dance. Since the student council cannot ask everyone they will Survey a group of students. Which sample can best help the council to draw conclusions about the preferences of all the students in the school.
A. 6 students from each grade
B. 25 students from each grade
C. 6 students from the entire school
D. 25 students from the entire school
1. Classify the equation 7x + 3 = 7x - 4
as having one solution, no solution, or
infinitely many solutions.
Answer:
No solution
Step-by-step explanation:
There are no values of x that make the equation true.
What is the slope of the line represented by the equation y = -x-3?
Answer:
(C) 1/3
Step-by-step explanation:
The slope intercept form: y = mx + b.
Note:
m = slope
b = y-intercept
x & y = (x , y) for the points.
You are trying to get the y-intercept of the following function given:
f(x) or y = (-2/9)x + (1/3)
1/3 is your answer, or (C), for 1/3 replaces the b inside the equation.
If you really need the slope, the slope of the following equation is (-2/9), which replaces the m inside the equation.
~
write square root of 64 - square root of -289 as a complex number in the form of a+bi
Answer:
[tex]\sqrt{64}-\sqrt{-289}[/tex]
[tex]=8-17i[/tex]
Step-by-step explanation:
[tex]\sqrt{64}=8[/tex] because 8(8)=64 and 8 is the positive square root of 64.
[tex]\sqrt{-289}=17i[/tex] because 17i(17i)=289i^2=-289(-1)=-289.
[tex]\sqrt{64}-\sqrt{-289}[/tex]
[tex]8-17i[/tex]
Answer:
8-17i
Step-by-step explanation:
Got right on PLATO
If a young blue whale gains about 200 pounds a day, how many pounds will the whale gain in 45 days
Answer:
9000
Step-by-step explanation:
200x45=9000
Answer:
9,000 pounds.
Step-by-step explanation:
That would be 45 * 200
= 9,000 pounds.
Evaluate
6
+
4
a
+
b
3
6+
a
4
+
3
b
6, plus, start fraction, 4, divided by, a, end fraction, plus, start fraction, b, divided by, 3, end fraction when
a
=
4
a=4a, equals, 4 and
b
=
3
b=3b, equals, 3.
Answer:
8
Step-by-step explanation:
what is the answer to 1/8÷1/4
1/8÷1/4
Flip over the second fraction
1/4=4/1
1/8 *4/1
Cross out 8 and 4 ,divide by 4
8/4=2
4/4=1
1/2 *1/1=1/2
Answer: 1/2
Answer:
1/2
Step-by-step explanation:
1/8 divided by 1/4 becomes
1/8 multiplied by 4/1
(When we divide fractions the second fraction flips and we multiply instead of division)
So the answer is 1/2
Suppose that each quarter at a particular community college Jared has to pay $785 in tuition and $23 in fees. If Jared has 2 quarters remaining find the total amount he will need for tuition and fees
Answer:
he will need exactly $808.75
Jared's total expense for the remaining 2 quarters would amount to $1616, which is the sum of tuition ($785) and fees ($23) per quarter, multiplied by the total remaining quarters (2).
Explanation:To determine the amount Jared will need for tuition and fees, we first have to calculate the total cost for each quarter. For every quarter, the total cost comprises of $785 in tuition and $23 in fees. Consequently, the overall cost per quarter will be 785 (for tuition) + 23 (fees), which amounts to $808.
Given that Jared still has 2 quarters remaining, the net amount he would require will be the product of the amount needed per quarter and the number of remaining quarters i.e., 808 * 2, therefore equally to $1616.
Learn more about tuition and fees calculation here:https://brainly.com/question/32938164
#SPJ2
1. Clare has a piece of paper that is 8 inches by 10 inches. How many pieces of paper
will Clare have if she cuts the paper in half n times? What will the area of each piece
be?
Answer:
2^n pieces
80 / (2^n) in²
Step-by-step explanation:
If she cuts the paper in half 1 time, she will have 2 pieces.
If she cuts the paper in half 2 times, she will have 4 pieces.
If she cuts the paper in half 3 times, she will have 8 pieces.
So the pattern is 2^n.
The original area is 80 in². Divided by 2^n pieces means each piece has an area of 80 / (2^n) in².
Please answer this correctly
Solve the following problems. Reduce your answers to their simplest form.
a. 13/41 + 27/82
b. 3 5/24 + 6 7/24 + 4 9/24
C. 5 2/3 + 29/69 + 6 21/23
d. 3 9/10 + 4/9 + 7/45 + 4
e. 6 - 7/15
f. 11 3/8 - 7/8
g. 7 1/6 - 3 4/9
h. 5 3/8 - 3 2/5
Answer:
a. 53/82
b. 13 7/8
c. 12 16/23
d. 8 1/2
e. 5 8/15
f. 10 1/2
g. 3 13/18
h. 1 39/40
Step-by-step explanation:
Step-by-step explanation:
a. 13/41 + 27/82
[tex]\frac{13}{41}+\frac{27}{82}[/tex]
[tex]\frac{13\times 82+27\times 41}{82\times 41}=\frac{53}{82}[/tex]
b. [tex]3\frac{5}{24} + 6\frac{7}{24} + 4\frac{9}{24}[/tex]
[tex]\frac{77}{24}+\frac{151}{24}+\frac{105}{24}[/tex]
[tex]\frac{77+151+105}{24}=\frac{333}{24}[/tex]
c) [tex]5\frac{2}{3} + \frac{29}{69} + 6 \frac{21}{23}[/tex]
[tex]\frac{17}{3}+\frac{29}{69} +\frac{159}{23}[/tex]
[tex]\frac{17\times 23}{3\times 23}+\frac{29}{69} +\frac{159\times 3}{23\times 3}[/tex]
[tex]\frac{17\times 23+29+159\times 3}{69}=\frac{897}{69}=\frac{13}{1}[/tex]
d) [tex]3\frac{9}{10} + \frac{4}{9} + \frac{7}{45} + 4[/tex]
[tex]\frac{39}{10} + \frac{4}{9} + \frac{7}{45} + \frac{4}{1}[/tex]
[tex]\frac{39}{10} +\frac{4\times 10}{1\times 10}+\frac{4\times 5}{9\times 5} + \frac{7}{45}[/tex]
[tex]\frac{39+1\times 10}{10}+ +\frac{4\times 5+7}{45}[/tex]
[tex]\frac{49}{10}+\frac{27}{45}[/tex]
[tex]\frac{49\times 45+27\times 10}{10\times 45}=\frac{11}{2}[/tex]
e)[tex]6-\frac{7}{15}[/tex]
[tex]\frac{6}{1}--\frac{7}{15}[/tex]
[tex]\frac{6\times 15-7\times 1}{1\times 15}=\frac{83}{15}[/tex]
f)[tex]11\frac{3}{8} - \frac{7}{8}[/tex]
[tex]\frac{91}{8}- \frac{7}{8}[/tex]
[tex]\frac{91-7}{8}=\frac{84}{8}=\frac{21}{2}[/tex]
g)[tex]7 \frac{1}{6} - 3\frac{4}{9}[/tex]
[tex]\frac{43}{6}-\frac{41}{9}[/tex]
[tex]\frac{43\times 9-41\times 6}{54}[/tex]
[tex]=\frac{141}{54}=\frac{47}{18}[/tex]
h)[tex]5\frac{3}{8}-3\frac{2}{5}[/tex]
[tex]\frac{43}{8}-\frac{17}{5}[/tex]
[tex]\frac{43\times 5-17\times 8}{8\times 5}=\frac{79}{40}[/tex]
What is the surface area of a sphere with a diameter of 8 mm?
Use 3.14 for π .
Answer:
Step-by-step explanation:
804.25mm
Match the property of equality with the example that models the property.
multiplication property of equality
55/11 = 11x/11
addition property of equality
3x - 4 + 4 = 12 + 4
subtraction property of equality
(4x)(1/4) = (3)(1/4)
division property of equality
(1/2) + 5x -(1/2)=8-(1/2)
Answer:
Each property is about an operation. Specifically, each property indicates that an equality is like a balance, if we operate one side, we must also operate the other side with the same operation and number.
So, the example that shows a division, that is representing the division property, and so on.
Division property of equality: this property states that if we divide one side of the equation, we must divide the other side by the same number.
[tex]\frac{55}{11}=\frac{11x}{11}[/tex]
Multiplication property of equality: this property states that if we multiply one side of the equation, we must multiply the other side by the same number
[tex](4x)(\frac{1}{4} )=(3)(\frac{1}{4} )[/tex]
Adition property of equality.
[tex]3x-4+4=12+4[/tex]
Subtraction property of equality.
[tex]\frac{1}{2}+5x-\frac{1}{2}=8-\frac{1}{2}[/tex]
The corret match is as follows:
Multiplication property of equality: (4x)(1/4) = (3)(1/4)
Addition property of equality : 3x - 4 + 4 = 12 + 4
Subtraction property of equality: (1/2) + 5x -(1/2)=8-(1/2)
Division property of equality: 55/11 = 11x/11.
For multiplication property of equality:
Consider an equation:
4x = 3
Multiply by (1/4) on both sides by this property we get,
(4x)(1/4) = (3)(1/4)
For addition property of equality:
Consider an equation:
3x - 4 = 12
Add 4 both sides we get,
3x - 4 + 4 = 12 + 4
For subtraction property of equality:
Consider an equation:
(1/2) + 5x=8
Subtract both sides by (1/2)
(1/2) + 5x -(1/2)=8-(1/2)
For division property of equality:
Consider an equation:
55= 11x
Divide both sides by 11 we get,
55/11 = 11x/11.
Hence,
The corret match is:
Multiplication property of equality: (4x)(1/4) = (3)(1/4)
Addition property of equality : 3x - 4 + 4 = 12 + 4
Subtraction property of equality: (1/2) + 5x -(1/2)=8-(1/2)
Division property of equality: 55/11 = 11x/11.
Learn more about the multiplication visit:
https://brainly.com/question/10873737
#SPJ3
Add using a number line. - 3/4 + 1 1/4 drag and drop the word SUM to the correct value on the number line.
PLEASE HELPPP
See the attached picture for the answer.
Write an algebraic expression for each word phrase.
3. 14 less than the quotient of 63 and a number h.
Answer:
63/h - 3.14
Step-by-step explanation:
Quotient means divide.
So the answer to the division is a quotient. 63/h is the quotient of the division.
Less means subtract so the subtraction that is taking place is
63/h - 3.14 and that's your answer.
Often with these questions, you start backwards as in this question.
3w - (7w + 12) = 2(w – 3)
how do u do this step by step
Answer:
w=-1
Step-by-step explanation:
3w-7w-12=2(w-3)
1) Combine alike terms:
-4w-12=2(w-3)
2) Use the Distributive property on the left side of the equation:
-4w+12=2w-6
3) Add a 6 to both sides:
-4w-6=2w
4) Add a 4w to both sides:
-6=6w
5) Divide both sides by 6:
w=-6/6
6) Simplify the fraction:
w=-1
The solution to the equation 3w - (7w + 12) = 2(w - 3) is w = -1.
The given equation is 3w - (7w + 12) = 2(w – 3).
Distribute the negative sign (-) to the terms inside the parentheses on the left side and distribute the 2 to the terms inside the parentheses on the right side:
3w - 7w - 12 = 2w - 6
-4w - 12 = 2w - 6
Move all the terms involving w to one side of the equation by adding 4w to both sides:
-4w + 4w - 12 = 2w + 4w - 6
-12 = 6w - 6
Add 6 to both sides of the equation to isolate the term with 6w:
-12 + 6 = 6w - 6 + 6
-6 = 6w
Divide both sides of the equation by 6 to solve for w:
(-6) / 6 = 6w / 6
-1 = w
Therefore, the solution to the equation 3w - (7w + 12) = 2(w - 3) is w = -1.
To learn more on Equation:
https://brainly.com/question/10413253
#SPJ6
how many times does 56 go into 432
complement of angle Y. Y=(8x-20°)
Answer:
Step-by-step explanation:
Complement = 90 - Angle
Complement = 90 - y
Complement = 90 - (8x - 20)
Complement = 90 - 8x + 20
Complement = -8x + 110
The complement of an angle Y denoted as (8x-20°), is found by subtracting the angle from 90°. After distribution and addition, the final formula for the complement of angle Y is 110° - 8x.
Explanation:The complement of an angle is defined as the difference between 90 degrees and the angle. In this case, we need to find the complement of angle Y, represented as (8x-20°).
To find the complement, we subtract the angle from 90°. So, the complement of angle Y is given by the formula 90° - (8x - 20°).
When you distribute the negative sign into the parentheses, the formula becomes 90° - 8x + 20°. Adding 90° and 20° gives us 110°, making the final formula for the complement of angle Y as 110° - 8x.
Learn more about the Complement of an angle here:
https://brainly.com/question/29775107
#SPJ2
f (x) = (x + 1)(x - 3)(x-4)
Factored form number of roots
There are 3 factors.
One root per factor.
Set each factor to 0 and solve for x individually.
Rewrite using the distributive property then solve. 3(5+7)
Answer:
36
Step-by-step explanation:
3(5+7)
multiply 3 and 5
then multiply 7 and 3
15 + 21
which is 36
Answer:
Step-by-step explanation: 3 x 5 =15 + 3 x 7 =21 15+21=36
solve 3(x-5)-4(x+3)=
3(x-5)-4(x+3)
Multiply the first bracket by 3
(3)(x)=3x
(3)(-5)=-15
(-4)(x)=-4x
(-4)(3)=-12
3x-15-4x-12
3x-4x-15-12 ( combine like terms)
Answer: -x-27
Are the listed ordered pairs on the graph for the function:
f(x) = 3x
Question 1 options:
6≠9therefore, not on the graph
3=3therefore, on the graph
27=27therefore, on the graph
3≠1therefore, not on the graph
1.
(0,3)
2.
(1,3)
3.
(2,6)
4.
(3,27)
2x+y=8
What is the work for it?
Answer:
y= -2x+8
Step-by-step explanation:
2x+y=8
-2x -2x
__________
y= -2x+8
I think this is what you're asking for. The question is kind of confusing.
Pleassseee help, and show steps
Answer:
(p +5)² = 26
Step-by-step explanation:
p²+10p = 1
try to arrange them like a²+2ab+b² ;
here,
a² = p² → ∴a=p
and,
2ab = 10p
⇒2ab = 10a [∵a=p]
∴ b=5 [dividing both sides by 2a]
∴b²=5²
hence,
⇒ p² + 2 .p.5 + 5² = 1+5² [add 5² on both sides ]
⇒ (p +5)² =1+25
∴ (p +5)² = 26
What is the image point of (9,8) after a translation right 4 units and up 2 units?
Answer:
(13,10)
Step-by-step explanation:
On the graph, all the points going right starting from 0, would be positive, and all points going up starting from 0 would be positive.
You should also know that going right would mean the x (which is 9 here) would get bigger; and the y (which is 4) going up would get bigger too.
So if you move (9,8) right 4 times 9 + 4 = 13, so now you have (13,8).
Then, you move (13,8) up 2 units, so 8+2 more units = 10, so then your final answer would be (13,10).
Hope this helped, sorry if its confusing I wasn't born to teach lol
The image point of (9, 8) is (13, 10), after the translation.
What is the required image point ?
In graphs, we know that the horizontal line is the x-axis, more we go right in that line, more positive values of x we get & in similar manner, more we go left, we get more negative values of x.
So, if we translate (9, 8), 4 units in the right, then we get larger value of x, i.e. 9+4=13 and the point becomes (13,8)
Also, the vertical line on a graph defined the y-axis, more we go up in that line, more we get positive values of y and more we go down that line, more we get negative values of y.
So, if we up the value of y 2 units, then the co-ordinate of y is 8+2 = 10
And the point becomes (13,10)
So, the required image point is (13,10)
Learn more about image point here :
https://brainly.com/question/2418777
#SPJ2
2a - 14 - 7b + 10
Select ALL coefficients from the expression above. I NEED AN ANWSER ASAP
its called be a smart kid and actually paying attention u downs syndrome idiot
Two angles are complementary. The measure of the larger angle is 10 more than 4 times the measure of the smaller angle. Find the measures of both angles.
Can someone please help me?
Answer:
16 = small
74 = big
Step-by-step explanation:
4x+10 = big angle
x = small angle
4x+10+x = 90
5x+10 = 90
5x = 80
x = 16
4 x 16 + 10 = 74
Avocado out!!!!!!!!!
Answer:
[tex]y=16^{\circ},x=74^{\circ}[/tex]
Step-by-step explanation:
Let complementary angles are x and y.
Let x is larger angle between x and y.
We have to find the measure of both angles x and y.
According to question
[tex]x=4y+10[/tex]
We know that complementary angles :Two angles whose sum is 90 degrees.
[tex]x+y=90^{\circ}[/tex]
[tex]4y+10+y=90[/tex]
[tex]5y=90-10=80[/tex]
[tex]y=\frac{80}{5}=16^{\circ}[/tex]
Substitute the value then we get
[tex]x=4(16)+10=74^{\circ}[/tex]
I WILL GIVE BRAINLIEST IF CORRECT!
Q1) what property is shown?
-8 + (-15) = (-15) + (-8)
A) distributive property
B) opposite of a sum property
C) commutative property
D) associative property
____________________________
Q4) what is the value of q makes the statement true?
-(q+14) = -3 + (-14)
A) 17
B) -17
C) -3
D) 3
____________________
what value of a makes the statement below true?
-10 + a + (-15) = 50
A) 25
B) -75
C) -25
D) 75
Answer:
(1).(C) Commutative property.
(4).(D) 3
(3).(D) 75
Step-by-step explanation:
(1) Commutative property of addition states that if two number p and q are real. Then, it doesn't matter in which order the numbers are added it will provide the same result. i.e.
p + q = q + p
Therefore, -8 + (-15) = (-15) + (-8) is an example of commutative property.
(2) - (q+14) = (-3) + (-14)
[tex]\Rightarrow -q - 14=-3 -14[/tex]
[tex]\Rightarrow-q= -17 +14[/tex]
[tex]\Rightarrow-q=-3[/tex]
[tex]\Rightarrow q=3[/tex]
(3) -10 + a + (-15) = 50
[tex]\Rightarrow a -25 = 50[/tex]
[tex]\Rightarrow a = 50 + 25 = 75[/tex]
Which equation or inequality correctly compares 15006.099 and 15006.101? A.15006.099<15006.101 B.15006.099>15006.101 C.15006.099 = 15006.101
Hey!
-------------------------------------------------
[tex]\boxed{ \bf A.~15,006.099~<~15,006.101}[/tex]
-------------------------------------------------
Explanation:
Since both numbers have 15,006 before the decimal we only need to see which number has a bigger decimal.
0.099 < 0.101
0.101 - 0.099 = 0.002
So, 15,006.101 is 0.002 bigger than 15,006.099!
-------------------------------------------------
Hope This Helped! Good Luck!
Convert 45°C to Fahrenheit using the formula F = 5 C + 32.
081°F
O 113°F
O 57°F
138.6°F
Question #25MultipleChoice
Answer:113
here you go
Answer:
113
Step-by-step explanation:
Here you go